فعالية برنامج إرشاد نفسي ديني لتعديل اتجاهات التلاميذ العاديين نحو المعاقين عقلياً بمدارس الدمج بالمرحلة الابتدائية - أبو حويلة، إسلام أحمد محمد; الشورى، فؤاد حامد الموافي; أحمد، ليلى عبدالعظيم المتولي سيد (جامعة المنصورة - كلية التربية, 2022)
هدفت الدراسة الحالية التعرف عن فعالية برنامج إرشادي نفسي ديني لتعديل اتجاهات التلاميذ العاديين نحو المعاقين عقلياً من خلال المجالات المتمثلة في: الاتجاه نحو سمات وخصائص المعاقين عقلياً, الاتجاه نحو التفاعل الاجتماعي مع المعاقين عقلياً, الاتجاه نحو حقوق ورعاية المعاقين عقلياً, الاتجاه نحو تعليم ودمج المعاقين عقلياً, وتكونت عينة الدراسة من (20) تلميذ/ تلميذة ممن تتراوح أعمارهم بين(11.6-12) سنة, تم تقسيمهم عشوائياً إلى مجموعتين: المجموعة التجريبية وتشمل(10) تلاميذ(7) ذكور و(3) إناث, والمجموعة الضابطة تشمل (10) تلاميذ(7) ذكور و(3) إناث, , بمتوسط عمر زمني قدرة(11,870) سنة, وانحراف معياري قدرة(440‚), ممن لديهم درجة منخفضة على مقياس الاتجاه نحو المعاقين عقلياً, وتكونت أدوات الدراسة من: مقياس الاتجاه نحو المعاقين عقلياً( إعداد الباحثة), والبرنامج الإرشاد نفسي ديني لتعديل اتجاهات التلاميذ العاديين نحو المعاقين عقلياً(إعداد الباحثة), واستخدمت الباحثة الأساليب الأتية: معامل ارتباط بيرسون (Pearson), معامل ألفا كرونباخ (Alpha – Chornbach), معادلة حجم التأثير, وذلك باستخدام برنامج الحزم الإحصائية (SPSS) إصدار (25), وقد أسفرت نتائج الدراسة عما يلي: وجود فروق دالة إحصائياً بين متوسطي رتب درجات المجموعة التجريبية والمجموعة الضابطة في القياس البعدي على مقياس الاتجاهات (المجالات و الدرجة الكلية) لصالح المجموعة التجريبية, وجود فروق دالة إحصائياً بين متوسطي رتب درجات المجموعة التجريبية في القياسين القبلي والبعدي على مقياس الاتجاهات(المجالات والدرجة الكلية) لصالح القياس البعدي, لا توجد فروق دالة إحصائياً بين متوسطي رتب درجات المجموعة التجريبية في القياسين البعدي و التتبعى على مقياس الاتجاهات لتلاميذ المرحلة الابتدائية, وجود حجم تأثير مرتفع للبرنامج الارشادي الديني المستخدم في تعديل الاتجاهات لدي المجموعة التجريبية, مما يدل على فعالية البرنامج الإرشاد نفسي ديني المستخدم في تعديل اتجاهات التلاميذ العاديين نحو المعاقين عقلياً. The current study aims to identify the effectiveness of a religious psychological counseling program to modify the attitudes of ordinary students towards the mentally disabled through the areas of: attitudes towards the features and characteristics of the mentally disabled, attitudes towards social interaction with the mentally disabled, attitudes towards the rights and care of the mentally disabled, and the attitudes towards the education and integration of the mentally disabled. The study sample consists of (20) male and female students, whose ages range between (11.6 - 12) years. They were randomly divided into two groups, namely the experimental group involving (10) students, (7) males and (3) females, and the control group consisting of (10) students, (7) males and (3) females, with an average age of (11,870) years, and a standard deviation of (0.440), who have a low measure of attitudes towards the mentally disabled. The study tools consisted of: a measure of the attitudes towards the mentally disabled (prepared by the researcher), and a religious psychological counseling program to modify the attitudes of ordinary students towards the mentally disabled (prepared by the researcher). The researcher used the following methods: Pearson correlation coefficient, Alpha Cronbach coefficient, and the impact size equation, using the Statistical Packages Program (SPSS), version (25). The study concluded that there are statistically significant differences between the mean scores of the experimental group and the control group in the post-measurement on the attitudes scale (domains and total score) in favor of the experimental group. There are statistically significant differences between the mean scores of the experimental group in the pre and post measurements on the attitudes scale (domains and total score) in favor of the post-measurement. There are no statistically significant differences between the mean scores of the experimental group in the post and follow-up measurements on the attitudes scale for primary school students. There is a high impact size of the religious counseling program used in modifying the attitudes of the experimental group, which indicates the effectiveness of the religious psychological counseling program used in modifying the attitudes of ordinary students towards the mentally disabled.
Keywords: البرامج الإرشادية -- الإرشاد النفسي -- ذوي الإعاقة -- الدمج التربوي -- طلبة المرحلة الابتدائية